Impact of "chemobrain" in childhood cancer survivors on social, academic, and daily living skills: a qualitative systematic review protocol. Issue 1 (2nd January 2022) - Semendric, Ines; Pollock, Danielle; Haller, Olivia J.; George, Rebecca P.; Collins-Praino, Lyndsey E.; Whittaker, Alexandra L.
ABSTRACT: Objective: The objective of this review is to examine children's experiences of chemotherapy-induced cognitive impairment (also known as "chemobrain") and the impact of chemobrain on children's social, academic, and daily living skills. Introduction: The effect of childhood chemotherapy treatment on cognition is of concern because of the vulnerable nature of children's developing brains and the potential to cause lifelong detriments socially, academically, and economically. Furthermore, this population is under-represented in the chemobrain literature and in survivorship care plans. As cancer survivorship among this group increases, it is important to understand childhood experiences so that rehabilitation strategies and suitable supports can be put in place. Inclusion criteria: This review of qualitative studies will focus on the pediatric population (0 to 18 years of age) during and/or following chemotherapy treatment to identify their experiences with chemobrain. The review will include any studies using a qualitative research methodology (eg, surveys, focus groups, interview transcripts), conducted in any geographic location, where experiences are presented from the child's perspective. Studies assessing children's experiences of cancer, other chemotherapy-related side effects, or the parent's personal experience will be excluded. Methods: A search of MEDLINE, Embase, PsycINFO, and CINAHL databases will be conducted. Full-text, English-only articles employing a qualitative research methodology will be included in the screening process. Two independent reviewers will retrieve and screen full-text studies, and assess methodological quality of the included studies. Meta-aggregation will be performed and a ConQual Summary of Findings will present the confidence in the findings. Systematic review registration number: PROSPERO CRD42021240573.